"The unfamiliar home" - Dellosa, Chloe P.
This thesis is about the exploration on the relationship of my immediate surroundings with the perception of home. Growing up within the setting of my father's occupation-which is carpentry, I learned to associate the sensations in that environment to my idea of home. The sight, smell, color and texture in my father's workshop became strongly instilled in my memories. Therefore, although we often moved to different houses, these materials interestingly anchor and give me a sense of home. home is important in the development of a person. Wendell Berry says in his quote "If you don't know where you are, you don't know who you are." This is further supported by archaeologist Julian Thomas, who defines place as an important element of human existence. Therefore, in this thesis I addressed the issue of finding a sense of home despite my frequent experience of movement from one house to another and a lack of a permanent place to dwell in. It poses an answer to my inquiry: how can the experience of my past living spaces be reconstructed to embody my sense of home through an experiential installation made primarily of wood shavings? To depict this, I used the element of space to construct an experiential installation which is aimed at focusing one's attention into my personal experience of home. Experiential art is an approach I used to transform these mundane objects in my home into a fresh new experience. inspired by the wood shaving's spiral structure which echoes continuity, I depict movement as a transient. As my experiences of homes are impermanent, so are these light and throwaway materials which are transitory in nature. In the process of constructing the piece, I also discovered the part of the significance of the work was the chance to reevaluate the present. Home is also about relationships. The presence of my father and his work as we moved surely had an impact on my artistic process. Through this artistic product, I have come to realize that the issue of not having a permanent settlement because of not having enough money to acquire one, became a basis for the idea of my art making. In a way, that lack of a physical and permanent structure of home was able to result to an installative work which is particular to my own experience and condition.